Self-employment and Migration - Samuele Giambra; David McKenzie (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
There is a widespread policy view that a lack of job opportunities at home is a key reason for migration, accompanied by suggestions of the need to spend more on creating these opportunities so as to reduce migration. Self-employment is widespread in poor countries, and faced with a lack of existing jobs, providing more opportunities for people to start businesses is a key policy option. But empirical evidence to support this idea is slight, and economic theory offers several reasons why the self-employed may in fact be more likely to migrate. We put together panel surveys from eight countries to descriptively examine the relationship between migration and self-employment, finding that the self-employed are indeed less likely to migrate than either wage workers or the unemployed. We then analyze seven randomized experiments that increased self-employment, and find their causal impacts on migration are negative on average, but often small in magnitude.
Keywords: F22; J61; O15; 330; internal migration; international migration; self-employment; migrant selection; randomized experiment